Food habits based on gender perspective in rural and urban of West Java - Fatchiya, Anna; Khomsan, Ali; Riyadi, Hadi; Mauludyani, Anna Vipta Resti; Nurhidayati, Vieta Annisa (Intelektual Pustaka Media Utama, 2024)
The role of women in food consumption decision-making is closely related to cultural norms. The primary objective of this study was to describe food habits based on gender perspective in West Java. This study used a cross-sectional design. The study was conducted for 12 months in Cianjur Regency (representing rural area) and City of Sukabumi (representing urban area), West Java, Indonesia. The samples were selected using clustered purposive sampling. The total subjects were 150 households. This study showed that in term of food allocation, fathers have privilege, such as fathers eat before mothers and children, setting aside foods for fathers first before sharing the rest with family members, and food menu that the father received was more complete or better. The wives have greater control than husband in aspects of household food management. The wives were also dominant in deciding food expenses in the family rather than their husbands. There were significant differences in food allocation between rural and urban areas. The differences including: fathers eat before mothers and children (p<0.001), menu differences between fathers and other family members (p=0.002), and menu differences among family members (p=0.008). There was a significant difference in decisions making to determine the daily food menu between rural and urban areas (p=0.004). Since mothers play an important role in food purchasing, improving nutrition knowledge is necessary for better quality food at the household level. This will have an impact on the nutritional status of all household members.